Professional Learning Communities’ Effectiveness in Teachers: Exploring the Language Use - Gobodwana, Anele; Rubela , Thanduxolo (Journal of Ecohumanism, 2025)
Teachers from the same local district engage in discussions about the subjects they teach. In manoeuvring, the best pedagogical approaches are employed, and as they meet, they use the language in those discussions. Department of Basic Education (DBE) has implemented PLCs, which have enhanced the effectiveness and relevance of teaching, aligning with the overarching goal of achieving educational success. This article aims to investigate whether language serves as an obstacle to discussions among multiple teachers. The emphasis on addressing the language issue is driven by the presence of multilingual teachers within a single classroom and shared meetings. This article draws on qualitative secondary data, utilizing document analysis as the primary method of data collection and analysis. A potential insight from this article is that language may indeed pose a barrier to academic interactions and discussions among teachers throughout the district. Finally, the practice of translanguaging should be embraced and valued in multilingual discussions.